Effects of the Essential oils of Iranian Medicinal Plants on the Growth of Some Pathogenic Bacteria - Aroiee*, H.; Mohsenzadeh, M.; Doloei, R. Rezaian; Mosapor, S.; Karimzadeh, H.; Eng.Co., Noghteh Atf (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The antimicrobial activities of the essential oils of four different medicinal plants (cumin, thyme, mint and fennel) were investigated on Escherichia coli, Klebsiella pneumonia, Proteus vulgaris, and Pseudomonas aeruginosa. The antimicrobial activity of the essential oils was evaluated by disc diffusion method. The results showed that the most effective oils were thyme (Thymus vulgaris L.) and peppermint (Mintae piperita). The use of theses essential oils, should be considered in the food preservation. Keywords: Essential oil, Escherichia coli, Proteus vulgaris, Klebsiella pneumonia, Pseudomonas aeruginosa, Antibacterial activity Corresponding author: E-mail: aroiee_h@yahoo.com